2014
DOI: 10.1038/ejcn.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to enteral nutrition in abdominal enterocutaneous fistula patients with Crohn's disease

Abstract: In CD patients with ECF, lower CRP and higher BMI are associated with higher possibility of closure after EN treatment. EN therapy can lead to a closure of ECF in a certain proportion of patients. EN therapy could also ameliorate inflammatory condition and improve nutrition status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…In a group of adult patients with inflammatory stricturing CD ( n = 59), EEN administered for 12 weeks achieved radiological remission of stricturing disease in 54% and resolution of clinical symptoms in 65% of patients . Similarly, in patients with enterocutaneous fistulae, two small studies have shown that 12 weeks of EEN led to fistula closure in 62.5–75% of patients . In those with intra‐abdominal collections, use of EEN for over 12 weeks was associated with resolution of collection in 76% of patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a group of adult patients with inflammatory stricturing CD ( n = 59), EEN administered for 12 weeks achieved radiological remission of stricturing disease in 54% and resolution of clinical symptoms in 65% of patients . Similarly, in patients with enterocutaneous fistulae, two small studies have shown that 12 weeks of EEN led to fistula closure in 62.5–75% of patients . In those with intra‐abdominal collections, use of EEN for over 12 weeks was associated with resolution of collection in 76% of patients .…”
Section: Resultsmentioning
confidence: 99%
“…26 Similarly, in patients with enterocutaneous fistulae, two small studies have shown that 12 weeks of EEN led to fistula closure in 62.5-75% of patients. 27,28 In those with intraabdominal collections, use of EEN for over 12 weeks was associated with resolution of collection in 76% of patients. 28 There are no data on EEN for perianal CD in adults, although there are several case reports describing efficacy in pediatric patients.…”
Section: Statement 1: Clinical Indications For Een Therapy In Adults mentioning
confidence: 99%
“…A preoperative lag allowed for amelioration of patient conditions – reducing the inflammatory environment [58-60], increasing serum albumin [59, 60], weaning or suspending CST therapy [57, 59], and treating abscesses [59, 60] – as opposed to patients operated on immediately [58, 59]. These properties have also been attributed to nutritional support, both enteral and parenteral, by other authors [44, 47, 48, 50, 52-54, 69-72]. Also, in one of the reviewed studies [59], going straight to surgery (non-EEN patients) was an independent risk factor for anastomotic leaks and/or intra-abdominal abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Most occur post-operatively. It is demonstrated that in surgical patients, early nutritional support, independently of the route of administration, decreases the occurrence and severity of fistulae [84,98,99]. Malnutrition with BMI <20 appears as an independent risk factor [100].…”
Section: Grade Of Recommendation B E Strong Consensus (96% Agreement)mentioning
confidence: 99%